The wind in the willows - Alexander, Robert; Rafel, Alan.; Wagner, Robin, 1933-; Slaiman, Marjorie, approximately 1925-2002.; Eggleston, William; Michele, Lorraine; Wayland, Newton; Grahame, Kenneth, 1859-1932.; Arena Stage (Organization : Washington, D.C.); Richard L. Coe Theater Programs Collection (Library of Congress) (London : Methuen, 1956)
Arena Stage musical theatre for children presents "The Wind in the Willows," by Kenneth Grahame, book and lyrics by Lorraine Michele, music by Newton Wayland, directed by Robert Alexander, musical director Alan Rafel, setting by Robin Wagner, costumes by Marjorie Slaiman, lighting by William Eggleston.
Arena Stage, December 26-30, 1966.
Title devised by Library staff.
Cast: Kathryn Tracy, Brendan Hanlon, David Congdon, Delores Wilson, Lillian Winkler, William Larson, Sarah Gorham, Valerie Mamches.
In: Richard L. Coe Theater Programs Collection (Library of Congress).
Keywords: English fiction; Theater programs -- Washington (D.C.); Theater programs -- 1966.